Ecologo-faunistic review of lamellicorn beetles (Coleoptera, Scarabaeoidea) of urbocenosis of Kharkov city (Ukraine) - O. V. Putchkov; T. Y. Markina; N. Komaromi (Biosystems Diversity, 2017)
This article presents a general overview of the superfamily Scarabaeoidea in five parks of Kharkov city and some adjacent agrocenosises. The species composition includes 32 species from four families of Scarabaeoidea. The Scarabaeidae family dominated in biodiversity and abundance (26 species from 16 genera). Six species (Dorcus parallelopipedus, Platyderes caraboides, Anoplotrupes stercorosus, Aphodius melanostictus, Pleurophorus caesus and Onthophagus coenobita) were sporadically registered as common, but in separate urban cenosises the number of species did not exceed one or three. The species composition and abundance of lamellicorn beetles was higher in large parks with only slight recreational disturbance. Here from 13 to 20 species were registered. On lawns in the center and in other districts of the city Scarabaeoidea species met very rarely. In the agrocenosises on the outskirts of Kharkov city – 16 species are noted, almost half of which were registered as common. The faunistic similarity of different urban cenosises was at low to medium levels (an average 0.20–0.47). These indices were slightly higher (0.38–0.67) for areas with lower recreational pressure. The indices of faunal similarity of separate parks and agrocenoses were lower (0.18–0.56, but on average – 0.33). At the level of common species, there was no faunistic similarity. The significance of such differences was due to both the low number of most Lamellicorn species and some of their ecological characteristics. The main differences were observed in the ratio of trophic groups and features of the spatial distribution of the dominant species. Smaller differences were observed on biotopic characteristic of most species. There were no differences in the hygropreference of the scarabeid species. In the parks herpetobiont saprophagous species dominated (mainly coprophagous and dendrophagous). In the agrocenoses, dendrochordobiontic phytophagous species predominated. The peculiarities of the ratio of different ecological groups of Scarabaeoidea in urban and agrocenosises are discussed.